2023
DOI: 10.53771/ijbpsa.2023.6.2.0119
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of home medication review in resolving drug-related problems in geriatric hypertensive patients: A community-based study

Satish S,
Fathima Shabna,
Ramakrishna Shabaraya A.

Abstract: Home Medicines Review (HMR) is a health care service aimed to address various home medication management (HMM) issues which includes multiple services like maximizing knowledge regarding disease and its management, resolving drug-related problems and improving adherence to therapy. HMM issues are highly prevalent in geriatric patients owing to their chronic diseases like hypertension. The main objective of the study was to assess the impact of HMR in hypertensive geriatric patients in Dakshina Kannada. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This behavior increases the risk of medication errors, pointing to an urgent need for strategies to enhance pediatric medication safety [7]. Although not directly focused on the pediatric population, a study assessing the efficacy of HMR in geriatric hypertensive patients demonstrated the effectiveness of this approach in resolving drug-related problems (DRPs), suggesting that similar benefits could be observed in younger populations [8]. Clinical pharmacist-led medication reviews in pediatric inpatients have shown potential in detecting DRPs, highlighting the importance of involving pharmacists in direct patient care to improve medication safety [9].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior increases the risk of medication errors, pointing to an urgent need for strategies to enhance pediatric medication safety [7]. Although not directly focused on the pediatric population, a study assessing the efficacy of HMR in geriatric hypertensive patients demonstrated the effectiveness of this approach in resolving drug-related problems (DRPs), suggesting that similar benefits could be observed in younger populations [8]. Clinical pharmacist-led medication reviews in pediatric inpatients have shown potential in detecting DRPs, highlighting the importance of involving pharmacists in direct patient care to improve medication safety [9].…”
Section: Discussionmentioning
confidence: 99%